Microbiological Risk Assessment of Listeria Monocytogenes in Minimally Processed Vegetables - S. Ponniah, P. Jeyaletchumi (2011)
The purpose of this study was to carry out a microbiological risk assessment on Listeria. monocytogenes in vegetables that are consumed in the minimally processed state in Malaysia. The prevalence and number of Listeria spp. and L. monocytogenes were determined in raw vegetables from pre-harvest and retail level. Environmental samples of soil, water and animal manure were also obtained from vegetable farms. Characterisation of strains isolated from vegetables was carried out by phenotypic (antibiotic resistance) and genotypic (Random Amplification of Polymorphic DNA) methods. A kitchen simulation study was conducted to provide decontamination and cross-contamination data and information for estimation of the risk of acquiring listeriosis from consumption of minimally processed vegetables using a step-wise risk assessment as well as a stochastic approach using simulation software. At the retail level, 306 vegetable samples were examined over a one-year period (February 2008 to January 2009). The prevalence of Listeria spp. was 33.3% while the prevalence for L. monocytogenes was 22.5 %. L. monocytogenes was frequently found in yardlong bean (n=32) at 31.3% and Japanese parsley (n=33) at 27.2%. At the farm level, 50 vegetable samples were taken. Both Listeria spp and L. monocytogenes were detected in 16% and 6 % of the samples respectively. Among the environmental samples (n=94), Listeria spp. and L. monocytogenes were detected in 47.6% and 38.1 (n=21) of soil samples; 77.8% and 61.1% of manure samples (n=18); 25% and 12.5% of environmental swabs (n=40). It was not however detected in samples of the irrigation water (n=15). From the kitchen simulation study, it was found that the mean percent transfer rate from vegetables (n=45) to the wash water ranged from 32.4% to 60.2%, from wash water to cucumber was 24.9% to 66.3%; from vegetables to chopping board was 18.9 to 32.2%; from chopping board to cucumber was 5.4 to 75.3%. Washing of the vegetables in tap water caused a 0.3-log reduction of L. monocytogenes attached to the vegetables. Characterization of 71 strains isolated from the 306 samples of vegetables was done by Random Amplification of Polymorphic DNA (RAPD). It was found that the strains could be grouped into 6 clusters and 1 solitary isolate. This shows that the strains that have been isolated demonstrate genetic variability and is of importance to the Microbial Risk Assessment as the different strains would have variations in virulence and pathogenicity. In terms of antimicrobial susceptibility, the Multiple Antibiotic Resistance Index (MARI) of the strains ranged from 0.06 to 0.63. Only 14 % of the strains had MARI values higher than 0.2. MARI values less than 0.2 indicate strains from origins where antibiotics are seldom or never used. The importance of the antimicrobial study to the Microbial Risk Assessment would be that some of the strains exhibit multi-resistance to drugs used in the treatment of listeriosis. The estimation of risk of acquiring listeriosis from consuming minimally processed vegetables was done using a deterministic and stochastic approach. An exponential dose-response model was used to estimate the probability of illness in low risk and high risk group of consumers. The estimated mean risk per serving for salads was 1.42 x 10-5 per 100 000 population for the healthy low-risk population. For the high risk group, the risk estimate was 1.23 x 10-2 per 100 000 population for AIDS patients, 3.55 x 10-4 per 100 000 population for diabetics and 1.09 x 10-4 per 100 000 population for the elderly population respectively. The exposure assessment model was most sensitive to the input distribution describing the serving size. This implies that the serving size was the input parameter that most strongly influenced the risk and would be the primary control option in trying to reduce risk. In conclusion, a risk assessment has been conducted that can lay the foundation for more comprehensive studies as well as alert health authorities to be more vigilant about listeriosis especially among the vulnerable population.